A phase I window, dose escalating and safety trial of metformin in combination with induction chemotherapy in relapsed refractory acute lymphoblastic leukemia: Metformin with induction chemotherapy of vincristine, dexamethasone, PEG‐asparaginase, and doxorubicin. Issue 9 (1st June 2018) - Trucco, Matteo; Barredo, Julio C.; Goldberg, John; Leclerc, Gilles M.; Hale, Gregory A.; Gill, Jonathan; Setty, Bhuvana; Smith, Tiffany; Lush, Richard; Lee, Jae K.; Reed, Damon R.
Abstract: Background: Acute lymphoblastic leukemia (ALL) remains a major cause of death in children. AMP‐activated protein kinase (AMPK) affects the unfolded protein response (UPR), leading to increased vulnerability to endoplasmic reticulum (ER) stress in ALL cells. In vitro, metformin causes ALL cell death via AMPK‐mediated inhibition of the UPR. It was evaluated whether ER stress could be induced in relapsed ALL through a phase I study investigating the safety and feasibility of metformin in combination with relapse induction chemotherapy. Procedure: Metformin was administered twice daily for 28 days in addition to vincristine, dexamethasone, PEG‐asparaginase and doxorubicin (VXLD). Dose escalation of metformin was evaluated using a 3+3 design. Pharmacokinetics (PK), pharmacodynamic (PD) evaluation of the AMPK and ER stress/UPR pathways, and treatment response were assessed. Results: Fourteen patients were enrolled; all were evaluable for toxicity. The recommended phase 2 dose (RP2D) was Dose level 2, 1, 000 mg/m 2 /day. A single dose‐limiting toxicity (DLT), hypoglycemia with acidosis, was observed at the RP2D and two DLTs, diarrhea and acidosis, were observed at Dose Level 3. Nine patients were evaluable for response as defined by the protocol, receiving at least 85% of planned metformin doses. Five complete remissions, one partial response, and one stable disease were observed. PD evaluation showed induction of ER stress, activation of AMPK, and inhibition of the UPR. Conclusions: The VXLD with metformin was tolerable with a RP2D for metformin of 1, 000 mg/m 2 /day and yielded responses in a heavily pretreated population. ER stress was induced and toxicities attributable to metformin occurred in all dose levels.